Clinic-pathological characteristics of colonic carcinoma in relation to localization and histologic type - Živković Vesna; Katić Vuka; Đorđević Biljana; Krstić Miljan; Pejović Svetlana; Petrović Aleksandar (Vojnosanitetski Pregled)
Background/Aim. A significant increase in colonic carcinoma has been analyzed in numerous clinic-pathological studies and genetics models. The aim of this study was to determinate the differences in clinic-pathological parameters of colonic carcinoma regarding localization and histological type. Methods. The study enrolled 124 patients who had undergone surgery for colorectal carcinoma at the Clinic of Surgery in the town of Nis within 2005. Paraffin sections were stained with Hematoxilin-eosin (H&E), High iron diamine-Alcian blue (HID-AB) (pH-2.5) and Alcian blue-Preiodic arid Shiff (AB-PAS) (pH-2.5) methods. From pathological report we used data regarding: localization (right or left colon), histological type, histological grade, and parameters which determinate the tumor stage. Results. The total number of patients with right-sided colonic carcinoma was 40 (32.36%) and 84 (67.74%) with left-sided colonic carcinoma. Histopathologically, 96 (77.42%) adenocarcinomas and 28 (22.58%) mucinous adenocarcinomas were verified. There were no statistically significant differences between the right-sided and left-sided colonic carcinoma regarding sex, age, histological grade and tumor stage (p > 0.05). Mucinous adenocarcinomas was statistically significantly more frequent in right-sided colon (35.00%) than in left-sided colon (16.67%) (p < 0.05). There were no statistically significant differences between adenocarcinomas and mucinous adenocarcinomas regarding sex and disease stage. In younger patients the percentage of mucinous adenocarcinomas (28.57%) compared to nonmucinous ones (11.46%) was significantlly higher (p < 0.05) than in older patients. Mucinous adenocarcinomas had statistically significantly more frequently poor differentiation in comparison to adenocarcinomas (46.43% versus 9.37%, p < 0.001). Conclusion. According to the presented results it can be concluded that the lower grade of differentiation of the colon adenocarcinoma and mucinous secretion are significantly often present in younger patients.